2008
DOI: 10.21236/ada478604
|View full text |Cite
|
Sign up to set email alerts
|

Apache Aviator Evaluation of Dual-Technology Night Vision Systems in Operation Iraqi Freedom (OIF) Urban Combat (Master's Thesis)

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. that natural signals, such as images, admit a sparse decomposition over a redundant dictionary leads to efficient algorithms for handling such sources of data. In particular, the design of well adapted dictionaries for images h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Much of the information regarding visual performance with HMDs has been gained through pilot surveys (Patterson et al, 2007;Heinecke et al, 2008;Hiatt et al, 2004;Rash, and Martin, 1988;Rash et al, 2004;Rash et al, 2002). While this literature has detailed and high-lighted problems users have with the monocular design of Figure 12-9.…”
Section: Helmet Integrated Display Sight (Hidss) With Partial-overlapmentioning
confidence: 99%
See 2 more Smart Citations
“…Much of the information regarding visual performance with HMDs has been gained through pilot surveys (Patterson et al, 2007;Heinecke et al, 2008;Hiatt et al, 2004;Rash, and Martin, 1988;Rash et al, 2004;Rash et al, 2002). While this literature has detailed and high-lighted problems users have with the monocular design of Figure 12-9.…”
Section: Helmet Integrated Display Sight (Hidss) With Partial-overlapmentioning
confidence: 99%
“…Most surveys of visual issues with the IHADSS were conducted during peace time. However, Heinecke et al (2008) surveyed Apache aviators using the IHADSS during urban combat in Operation Iraqi Freedom. Their results generally paralleled those from other surveys.…”
Section: Helmet Integrated Display Sight (Hidss) With Partial-overlapmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the shift in the role of the AH-64 attack helicopter, the study concluded with a recommendation for a future investigation that would encompass AH-64 pilots operating in the urban combat environment. 9 This recommendation was pursued by Heinecke et al, 10 who repeated a variant of the OIF Study in 2006. This study again found reduced frequencies of reports of visual complaints, consistent with the 2003 OIF study.…”
Section: Figure 11 Cohort Study Logomentioning
confidence: 99%
“…The period post-9/11 allowed for studies during actual combat operations to determine if peacetime training and combat flight environments differed. [9][10] In this current report, the authors have reviewed the extant literature and provide a summary of the seminal studies investigating visual performance and perception issues performed over the past three decades.…”
Section: Introductionmentioning
confidence: 99%